Mendesain Pembelajaran dengan Model Discovery Learning Perbantuan Eddpuzzle dalam Optimalisasi Berpikir Kritis Matematis Siswa SMP - Azhad, Sugestiana; Yani, Nur Fitri; Nuriadin, Ishaq (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to determine the effectiveness of the Discovery Learning model assisted by the Edpuzzle application to improve students' mathematical thinking skills. The type of research used was qualitative research. The technique used by the researcher is a literature study, which means that the researcher sees and reviews articles related to the topic that the researcher takes. Data collection carried out by researchers is that researchers collect data from various sources such as books, journal articles in which are related to the topics taken, namely designing the Discovery Learning learning model assisted by Ed Puzzle in optimizing critical thinking for junior high school students. The results of the research, in the Discovery Learning Model students can find their own learning concepts so that students are forced to be active and the teacher acts as a facilitator only. To develop students' critical thinking skills in mathematics, they will develop after being given this DL learning model. In conclusion, the learning model using Discovery Learning can optimize students' critical thinking skills. The Discovery Learning learning model is very effective to be implemented in the teaching and learning process in the classroom. Students become more active in finding concepts, so that they can improve students' critical thinking, especially in mathematics. Keywords: Critical Thinking, Covid 19, Discovery Learning, EdPuzzle